Psychological Impact of Covid-19 on Orthodontic Patients - Sadia Nisar, Saada Nawaz, Somia Amin, Zarafshan Naseem, Sidra Qadir, Aleena Abbas (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Unexpected postponement or delay in various treatment protocols during peak time of COVID-19 cause serious psychological trauma and obstacle to orthodontists and orthodontic patients as well. Objective: To evaluate depression and anxiety level of orthodontic patients during this chaos regarding their treatment even when the treatment was resumed. Study Design: Questionnaire-based cross-sectional study. Place and Duration of Study: Department of Orthodontics, Bacha Khan College of Dentistry, Mardan from 1st July 2021 to 31st December 2021. Methods: One hundred and sixty-six orthodontic patients were enrolled after taking informed consent from the patients. Data were taken in hard form and then later verbally translated into native language of this area. Numerical rating scale was used for psychological assessment and for the determination of anxiety level where 0 refers to no anxiety and 10 interprets extreme anxiety. Results: Ninety-three females and seventy-three males were present in this study. Conclusion: Severe anxiety level was reported and patients were greatly concerned about their health.